TL and OSL study of Li2B4O7:Cu,Ag synthesized by combustion and solid-state reactions - Lucas Mateus Ferreira de Amorim; Viviane Khoury Asfora; Raquel Aline Pessoa; Vinicius Saito Monteiro de Barros; Pedro Luiz Guzzo; Helen Jamil Khoury (Brazilian Journal of Radiation Sciences)
The aim of this work was to investigate the Thermoluminescence (TL) and the Optically Stimulated Luminescence (OSL) responses of Li2B4O7: Cu, Ag synthesized using two method: a) solid-state and b) liquid combustion methods. In both procedures 0.4% mol of CuN2O6.3H2O and 0.1%mol of AgNO3 were used as dopants. The techniques of X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used for structural and morphological characterization. The results showed that the samples synthesized using the combustion method are mostly formed by Li2B4O7:Cu,Ag, while those produced by the solid-state method showed the presence of LiBO2. This fact affects the luminescence response of the samples, Those produced by combustion have higher TL and OSL sensitivities. The IRSL response was not observed for both sample’s batch. Future studies will be carried out to evaluate the use of Li2B4O7:Cu,Ag synthesized by solid-state for high dose dosimetry.